Increase in Central Venous Pressure During Passive Leg Raising Cannot Detect Preload Unresponsiveness. Issue 8 (August 2020) - Hamzaoui, Olfa; Gouëzel, Corentin; Jozwiak, Mathieu; Millereux, Maude; Sztrymf, Benjamin; Prat, Dominique; Jacobs, Frederic; Monnet, Xavier; Trouiller, Pierre; Teboul, Jean-Louis
Abstract : Objective: By analogy with the classical central venous pressure rules to assess a fluid challenge, we hypothesized that an increase in central venous pressure greater than or equal to 5 cm H2 O (i.e., 4 mm Hg) during passive leg raising can predict preload unresponsiveness diagnosed by the absence of increase in velocity-time integral of the left ventricular outflow tract greater than or equal to 10% during the test (negative passive leg raising test). Design and Settings: Velocity-time integral was measured by transthoracic echocardiography. Central venous pressure and velocity-time integral were measured before and during passive leg raising. Patients: Critically ill patients for whom the physician decided to test preload responsiveness by passive leg raising were prospectively included. Measurement and Main Results: Fifty-seven set of measurements were performed in 50 patients. Preload unresponsiveness (negative passive leg raising test) was observed in 32 cases. The changes in central venous pressure during passive leg raising did not differ between positive passive leg raising cases (positive passive leg raising test) and negative passive leg raising test cases (3 ± 2 vs 3 ± 2 mm Hg, respectively) and thus did not predict preload unresponsiveness (area under the receiver-operating characteristic curve of 0.59). An increase in central venous pressure greater than or equal to 4 mm Hg during passive leg raising was observed in 10 cases of positive passive leg raising test and in 11 cases of negative passive leg raising test. Taking an increase in central venous pressure greater than or equal to 3 or greater than or equal to 5 mm Hg rather than greater than or equal to 4 mm Hg during passive leg raising did not better allow one to identify negative passive leg raising test. Conclusions: Marked increase in central venous pressure during passive leg raising cannot identify negative passive leg raising test cases and thus preload unresponsiveness. Measurements of cardiac output (or its surrogates) during passive leg raising are, thus, mandatory to appropriately interpret this test. Abstract : Supplemental Digital Content is available in the text.